2018
DOI: 10.1021/acs.estlett.8b00482
|View full text |Cite
|
Sign up to set email alerts
|

Aerated Electrolysis for Reducing Impacts of Shale Gas Production Wastewater on Water Sources regarding Disinfection Byproduct Formation

Abstract: Advances in treatment technologies of shale gas production wastewater are needed to minimize its toxic potency in polluted water sources. An aerated electrolysis (AE) process was employed for treatment of both synthetic and field production wastewaters. Results showed AE led to a 64% reduction in the formation of total disinfection byproducts (DBPs) analyzed in this study and 79% reduction in the formation of more toxic brominated DBPs (Br-DBPs) in polluted natural water in an 8-h treatment, suggesting a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…There have been arising concerns about the formation and toxicity of unintended halogenated disinfection byproducts (DBPs) in chlorine disinfection of drinking water. Epidemiological studies have shown an association of the increased cancer risks and adverse reproductive outcomes to the human intake of DBP-containing tap water. , Two major halogenated DBP groups, trihalomethanes (THMs) and haloacetic acids (HAAs), have been regulated by the U.S. Environmental Protection Agency . In chlorine disinfection, natural organic matter (NOM) in source water, and organic matter from algal blooms or upstream wastewater discharge are chlorine consumers and viewed as precursors of regulated halogenated DBPs (including THMs and HAAs) and emerging DBPs. , As the most widely concerned DBP precursor, NOM is a complex mix of organic matter whose molecular structure and chemical composition change with time and location . Because of the heterogeneous nature of NOM, the commonly applied treatment processgranular activated carbon (GAC) adsorptionremoves only a small portion of NOM, and hence, it may not control overall halogenated DBPs in finished waters very effectively.…”
Section: Introductionmentioning
confidence: 99%
“…There have been arising concerns about the formation and toxicity of unintended halogenated disinfection byproducts (DBPs) in chlorine disinfection of drinking water. Epidemiological studies have shown an association of the increased cancer risks and adverse reproductive outcomes to the human intake of DBP-containing tap water. , Two major halogenated DBP groups, trihalomethanes (THMs) and haloacetic acids (HAAs), have been regulated by the U.S. Environmental Protection Agency . In chlorine disinfection, natural organic matter (NOM) in source water, and organic matter from algal blooms or upstream wastewater discharge are chlorine consumers and viewed as precursors of regulated halogenated DBPs (including THMs and HAAs) and emerging DBPs. , As the most widely concerned DBP precursor, NOM is a complex mix of organic matter whose molecular structure and chemical composition change with time and location . Because of the heterogeneous nature of NOM, the commonly applied treatment processgranular activated carbon (GAC) adsorptionremoves only a small portion of NOM, and hence, it may not control overall halogenated DBPs in finished waters very effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lower reduction potential of bromide than that of chloride, bromide was successfully oxidized to bromine, which was then stripped out by air bubbling without forming chlorine. Tang et al further investigated its impact on DBP formation and found that this process can reduce 64% of total DBPs and 79% of the brominated DBPs investigated . However, the bromide removal efficiency requires further improvement given that the removal of 15 mM bromide took up to 6.5 h in the lab-scale tests .…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al further investigated its impact on DBP formation and found that this process can reduce 64% of total DBPs and 79% of the brominated DBPs investigated. 23 However, the bromide removal efficiency requires further improvement given that the removal of 15 mM bromide took up to 6.5 h in the lab-scale tests. 22 Another study employed hybrid physical adsorption and capacitive deionization using activated carbon cloth electrodes, and the bromide desalination capacity was almost 2 orders of magnitude higher than that of chloride when bromide and chloride were at the same concentration (50 mM).…”
Section: ■ Introductionmentioning
confidence: 99%